Inside the Minds of Traders: Strategi Komunikasi Pemasaran para pedagang di Pasar Tradisional Karang Jasi, Kota Mataram - Astraguna, I Wayan (UHN IGB Sugriwa Denpasar, 2024)
The Karang Jasi market is a miniature of socio-cultural behavior and community economic activities in the city of Mataram, West Nusa Tenggara Province. Product marketing activities on the market traditional Karang Jasi is very competitive, thus every business actor must know how effective marketing communication strategies in increasing sales. This research was analyzed using a qualitative descriptive approach data collection using observation techniques, interviews and documentation with The analysis uses three stages, namely 1) data reduction, 2) data display, and 3) verification Data. The results of the research show that an effective marketing communication strategy is carried out by traders in the Karang Jasi market is by direct marketing techniques Marketing and personal selling which is an integrated marketing communication strategy. The conclusion that an effective marketing strategy that can be done by the sword In the Karang Jasi market, besides the integrated marketing strategy, there are other strategies that are used by traders in increasing sales, namely:1) Understanding the mindset of traders, 2) Customer retention in the Karang Jasi market, 3) Sellers build relationships with buyers, and 4) Sellers build customer trust by providing good service